Is There a Risk-Return Trade-Off across Occupations? : Evidence from Spain - Luis Diaz-Serrano; Joop Hartog (Institute for the Study of Labor (IZA), 2004)
We use data from Spain to test for an effect of earnings risk and skewness on individual wages. We carry out separate estimation for men, women, public and private sector employees. In accordance with previous evidence for the US we show the existence of a riskreturn trade-off across occupations in the Spanish labour market. These results are in conformity with preferences of risk-averse individuals with decreasing absolute risk aversion.
Keywords: D8; J3; 330; risk-aversion; skewness affection; occupational choices; compensating wage differentials; Lohnstruktur; Beruf; Risikoaversion; Schätzung; Spanien